Impact of Resin-Based versus Glass Ionomer Restorations on Adjacent Gingival Tissues in Cervical Lesions - Mobeen Akhtar, Sadiq Amin Ahmed Rana, Atikah Saghir Muhammad Abdul Wajid Khan, Jiand Malik, Mehvish Saleem, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Restorative materials in class V cervical lesions may influence adjacent gingival tissues. Thisexperimental randomized clinical trial compared resin-based composite (RBC) and resin-modifiedglass ionomer cement (RMGIC) restorations for their effects on gingival inflammation